A Centralized Platform for Geo-Distributed PACS Management. - Silva, Luís; Pinho, Renato; Ribeiro, Luís; Costa, Carlos; Oliveira, José (Journal of Digital Imaging, 2014)
Picture Archive and Communication System (PACS) is a globally adopted concept and plays a fundamental role in patient care flow within healthcare institutions. However, the deployment of medical imaging repositories over multiple sites still brings several practical challenges namely related to operation and management (O&M). This paper describes a Web-based centralized console that provides remote monitoring, testing, and management over multiple geo-distributed PACS. The system allows the PACS administrator to define any kind of service or operation, reducing the need for local technicians and providing a 24/7 monitoring solution.